Latest developments in the field of solar thermal standardisation - Fischer, S. (2012)
The European project QAiST-―Quality Assurance in Solar Thermal Heating and Cooling Technology‖ funded by the Intelligent Energy Europe program and by the participating countries, gathers 15 participating organizations including the European Solar Thermal Industry Federation ESTIF and major testing and research institutes in Europe. The objective of the project is to enhance the competitiveness of the European Solar thermal industry and further increase consumer confidence through improved standards and certification schemes, harmonization in testing and certification and a wide dissemination of the quality concept throughout Europe. Global harmonization in collector standards and certification is also on the QAiST agenda and has taken a large step forward through CEN/ISO cooperation and a strong European representation in the IEA SH&C task 43.